High Speed Evanescent Quantum‐Dot Lasers on Si. Issue 8 (27th June 2021) - Wan, Yating; Xiang, Chao; Guo, Joel; Koscica, Rosalyn; Kennedy, MJ; Selvidge, Jennifer; Zhang, Zeyu; Chang, Lin; Xie, Weiqiang; Huang, Duanni; Gossard, Arthur C.; Bowers, John E.
Abstract: Significant improvements in III–V/Si epitaxy have pushed quantum dots (QDs) to the forefront of Si photonics. For efficient, scalable, and multifunctional integrated systems to be developed, a commercially viable solution must be found to allow efficient coupling of the QD laser output to Si waveguides. In this work, the design, fabrication, and characterization of such a platform are detailed. Record‐setting evanescent QD distributed feedback lasers on Si with a 3 dB modulation bandwidth of 13 GHz, a threshold current of 4 mA, a side‐mode‐suppression‐ratio of 60 dB, and a fundamental linewidth of 26 kHz, are reported. The maximum temperature during the backend III/V process is only 200 °C, which is fully compatible with CMOS process thermal budgets. The whole process is substrate agnostic and hence can leverage previous development in QD lasers grown on Si and benefit from the economy of scale. The broadband and versatile nature of the QD lasers and the Si‐on‐insulator low‐loss waveguiding platform can be expanded to build fully functional photonic integrated circuits throughout the O band. Abstract : Record‐setting quantum dot (QD) distributed feedback lasers on Si are reported, with a 3‐dB modulation bandwidth of 13 GHz, a threshold current of 4 mA, a side‐mode‐suppression‐ratio of 60 dB, and a fundamental linewidth of 26 kHz. The broadband QD lasers and the Si‐on‐insulator waveguiding platform can be expanded to build fully functional photonic integrated circuits throughout the O band.